(3Pjd GdYHQs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efgG CKfGA SfI (B714 (3bhdg (B: (3ehdOg ai Chd jhe ef SJI CQHY hKdGKjf hcGf dGHCS Hg heGJ HMdH HGfJgGFgG Sja GdOjf ShOi s
(3BNQgG (B:s
(3ef SfI CQHYjf hSHY eFI , bhdg heGJJ SjOI GdTGe Ce eMeO RjfH HfJ GdceGd CMeO Hf YHO GdQMje GdebOSjI QhJ Yf eMeO Hf YHO GdgGOi BNQ eG hLO ef GdPjd s
(3Pjd ajg Ydi cJGHg GdYHO ai NHQ ef ZjQ GdPi GfJgi ajg Edi SfI (B700 (3g` hjHOC GdPjd ef SfI (B701 (3hjfJgi Edi SfI (B740s
(3ai GdeYgO fSNI CNQi HQbe (B1059 (3JGQjNs
(3cJHJ Hbde eged GdfbW ZGdjkGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
Keywords: (3GdJGQjNs